Parents’ Comprehension and Consideration Before Putting the Children Into Pre-School - Aprillya Alwien Suoth (English Education Postgraduate Program, Universitas Negeri Manado, 2022)
Comprehension and considerations of parents that needed before put the children into preschool. Nowadays, many parents want to put their children into early childhood education, like Preschool. All of the partial of early childhood education, like teacher, preschool (institute or school), and especially parents are expect their children to get a good achievement or good progress in learning education. Preschool is an early childhood program in which children combine learning with play in a program run by professionally trained adults. This research aimed to help the teacher, parents and preschool to understand their role and contribution to gain the successful and effectiveness of learning process in early childhood education. Especially to help parents to take a right comprehension and consideration that needed for they to know, before put their children into preschool. Remembering in the reality there is still lack of knowledge from parents, teacher, and pre-school institutions to apply their role. This article was using library research. The data were collected from several sources such as journal articles, literature. This article showed right comprehension and considerations by parents before put children into preschool are important, because it could help parent and children to be selectively choose the institutional of preschool that provide they needed. Remembering every child had different needs. This article could help parents to identify the basics that should provide by preschool, including the good materials, activities, place hygiene, character education, and moral values.